Isobaric Tags for Relative and Absolute Quantification-Based Proteomics Reveals Candidate Proteins of Fat Deposition in Chinese Indigenous Sheep With Morphologically Different Tails - Zhu, Caiye; Cheng, Heping; Li, Na; Liu, Tiaoguo; Ma, Youji (Frontiers in Genetics, 2021)
Background: Chinese indigenous sheep can be classified into two types according to their tail morphology: fat-rumped and thin-tailed sheep, of which the typical breeds are Altay sheep and Tibetan sheep, respectively. Methods: To identify the differentially expressed proteins (DEPs) underlying the phenotypic differences between tail types, we used isobaric tags for relative and absolute quantification (iTRAQ) combined with multi-dimensional liquid chromatography tandem-mass spectrometry (LC-MS/MS) technology to detect candidate proteins. We then subjected these to a database search and identified the DEPs. Finally, bioinformatics technology was used to carry out Gene Ontology (GO) functional and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses. Results: A total of 3,248 proteins were identified, of which 44 were up-regulated and 40 were down-regulated DEPs. Analyzing their GO function terms and KEGG pathways revealed that the functions of these DEPs are mainly binding, catalytic activity, structural molecule activity, molecular function regulator, and transporter activity. Among the genes encoding the DEPs, APOA2, GALK1, ADIPOQ, and NDUFS4 are associated with fat formation and metabolism. Conclusion: The APOA2, GALK1, ADIPOQ, and NDUFS4 genes may be involved in the deposition of fat in the tail of sheep. This study provides a scientific basis for the breeding of thin-tailed sheep.